Susceptibility of HLA-E*01:03 Allele Carriers to Develop Cytomegalovirus Replication After Living-Donor Kidney Transplantation. (8th December 2017) - Guberina, Hana; da Silva Nardi, Fabiola; Michita, Rafael Tomoya; Dolff, Sebastian; Bienholz, Anja; Heinemann, Falko M; Wilde, Benjamin; Trilling, Mirko; Horn, Peter A; Kribben, Andreas; Witzke, Oliver; Rebmann, Vera
Abstract : Cytomegalovirus (CMA) causes serious complications after transplantation. Genetic biomarkers are required for an improved individualized CMV-associated risk management. This study introduces HLA-E*01:03 allele carrier status, independent of CMV high-risk status, in transplant recipients as a prognostic factor for CMV infection after transplantation. Abstract: Cytomegalovirus (CMV) causes serious complications among solid organ transplant recipients. We report the positive correlation between the presence of the HLA-E*01:03 allele in living-donor kidney recipients and CMV reactivation during the first year after transplantation. Thus, HLA-E genotyping may help identify CMV replication–prone patients who require individualized patient-based CMV management.